The capacity to forgive from a psychological perspective - Casullo, María Martina (2005)
The capacity to forgive from a psychological perspective.A scale developed to assess the capacity to forgive, administered to 800 adults (50% males and 50% females) from the general population of the city of Buenos Aires and its suburban area (N: 8(0), is presented. Preliminary research data related to gender, age and religiosity are analyzed, as well as different psychological and philosophical conceptions. We found that women show a higher capacity to forgive than men and that forgiveness is associated to the presence of beliefs about it. According to our results, 88% of men and 95% of women consider that it is important to be able to forgive.